The proliferation of electronic public participation and the perpetual digital inequalities in South African regions - John Mamokhere (CV. Literasi Indonesia, 2026)
The Fourth Industrial Revolution (4IR) has accelerated digital transformation, creating opportunities for governments to enhance efficiency, transparency, accountability, public participation, and service delivery through digital technologies. In South Africa, electronic public participation (e-participation) has emerged as a strategic mechanism for strengthening public participation in municipal governance and the Integrated Development Planning (IDP) process. However, persistent digital inequalities continue to undermine these opportunities, particularly in rural municipalities across Limpopo, the Eastern Cape, and KwaZulu-Natal. This study investigates the structural and socio-economic factors perpetuating digital inequalities and their implications for inclusive e-participation in rural South African regions. A qualitative research approach was adopted, using thematic content analysis to examine evidence from appropriate municipalities. The findings reveal that municipalities such as Mkatazo Village, Mbhashe, Amathole, OR Tambo, Vhembe, and uMkhanyakude continue to experience inadequate broadband infrastructure, unreliable electricity supply, outdated digital systems, high data costs, limited access to digital devices, low digital literacy, language barriers, weak institutional capacity, limited political support, and constrained financial resources. Gender and age disparities further exacerbate digital exclusion. The study concludes that e-participation cannot realise its transformative potential without addressing these structural barriers. It recommends sustained investment in digital infrastructure, affordable connectivity, community-based digital literacy programmes, inclusive and localised e-participation models, strengthened institutional capacity, and stronger political commitment to embed e-governance reforms within municipal operations, thereby promoting equitable, inclusive, and sustainable digital governance in the 4IR era.